THE STUDENTS’ ENGLISH SPEAKING SKILL WITH BLENDED LEARNING OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 4 LAHEWA - Waruwu, Dodi Kardo Wijaya; Telaumbanua, Kristof Martin Efori; Telaumbanua, Yasminar Amaerita; Harefa, Trisman (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
This study aims to describe the English speaking skills of eighth-grade students at SMP Negeri 4 Lahewa through the implementation of a blended learning model. Employing a qualitative descriptive method, this research involved 22 students, with data collected through observation, interviews, and oral tests. The findings indicate that students' speaking skills generally range from a fair to a good level. Quantitative analysis of the oral test results reveals average scores of 2.8 for pronunciation, 2.5 for grammar, 2.4 for vocabulary, 2.3 for fluency, and 3.0 for comprehension. While most students demonstrated a decent understanding of spoken English, significant challenges persist in vocabulary retention, grammatical accuracy, and fluency. Students perceive blended learning as engaging and flexible; however, they express a preference for face-to-face interaction due to the opportunity for direct speaking practice. The study concludes that although the blended learning model shows promise, it requires further optimization, particularly in designing interactive online components, to effectively enhance students' productive language skills.   ABSTRAK Studi ini bertujuan untuk mendeskripsikan kemampuan berbicara bahasa Inggris siswa kelas delapan di SMP Negeri 4 Lahewa melalui implementasi model pembelajaran campuran (blended learning). Dengan menggunakan metode deskriptif kualitatif, penelitian ini melibatkan 22 siswa, dengan data yang dikumpulkan melalui observasi, wawancara, dan tes lisan. Hasil penelitian menunjukkan bahwa kemampuan berbicara siswa secara umum berkisar dari tingkat cukup baik hingga baik. Analisis kuantitatif hasil tes lisan menunjukkan skor rata-rata 2,8 untuk pengucapan, 2,5 untuk tata bahasa, 2,4 untuk kosakata, 2,3 untuk kelancaran, dan 3,0 untuk pemahaman. Meskipun sebagian besar siswa menunjukkan pemahaman yang baik tentang bahasa Inggris lisan, tantangan signifikan masih ada dalam retensi kosakata, ketepatan tata bahasa, dan kelancaran. Siswa menganggap pembelajaran campuran menarik dan fleksibel; namun, mereka lebih menyukai interaksi tatap muka karena adanya kesempatan untuk praktik berbicara langsung. Studi ini menyimpulkan bahwa meskipun model pembelajaran campuran menjanjikan, model ini membutuhkan optimasi lebih lanjut, khususnya dalam merancang komponen daring interaktif, untuk secara efektif meningkatkan kemampuan berbahasa produktif siswa.